The history of political thought: from Grands Doctrinnaires to the Social History of ideas - Lopes, Marcos Antônio (Tempo Social, 2002)
Analysis of the development in the history of the political ideas in the XXth century. The principal aspects accentuated in this paper refer to the conquest of institutional recognition of the intellectual history and its progressive opening in the contacts with other theoretical areas, elements that helped her to modernize, mading in the theoretical sophistication that is observed now in this horizon of studies.